ANALISIS PERKEMBANGAN LAPORAN KEUANGAN PT TASPEN (PERSERO) CABANG MATARAM DENGAN MENGGUNAN METODE COMMON SIZE DAN TREND - Lalu Mimbar (Sekolah Tinggi Ilmu Ekonomi AMM, 2016)
This study aims to analyze the development of the financial statements. TASPEN (Persero) Branch Mataram if analyzed using the vertical analysis (common size) and trend analysis. This type of research is descriptive, namely data analysis vertical analysis, horizontal analysis, and trend analysis. The results showed that, the form of financial statements. TASPEN (Persero) Branch Mataram are good and in accordance with the Financial Accounting Standards established by the Indonesian Institute of Accountants. The analysis of the use of common methods and trends in the balance sheet size PT.Taspen (Persero) Branch Mataram exceed the criteria expected. This is caused by PT. TASPEN (Persero) Branch Mataram tend to allocate their funds on investment activity in its business activity. Based on the analysis of the use of methods common size and trends in income PT. TASPEN (Persero) Branch Mataram decrease of criteria that is expected .akibat of a change in the value of the elements of assets and liabilities elements are not balanced. Results of the analysis based on the method trend towards reporting Income is income of the current year in 2011 increased by 99.68% from 2010, whereas in 2012 also increased by 76.36% from 2010. The increase is due to an increase earnings from 2010 that is equal to 128.73% in 2011 and 143.55% in 2012